PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIKA SISWA KELAS VIII DI SMP NEGERI 10 PADANGSIDIMPUAN - Agus Makmur Panjaitan; Erwina Azizah Hasibuan (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2018)
This study aims to find out the improvement of students critical thinking skills with the application of Contextual Teaching and Learning (CTL) model on the subject matter of two linear equations system to mathematics learning in class VIII at SMP Negeri 10 Padangsidimpuan.This study is a quasi experimental research using two class, one as experimental class and one as control class. The technique used in research sampling is cluster random sampling, that is experimental class using contextual teaching and learning model and control class using conventional learning model.The result of research indicate that critical thinking thinking of student mathematics has been done with Contextual Teaching and Learning (CTL) with an average of 78.48%, while with direct learning model with an average of 70.92%. In addition, hypothesis testing using t test with a significant level of 0.05 obtained the value of test Fa> Ftable = 2.269 with the value Ftable = 2.028. Because Fcount> Ftable, the decision of rejection test H0 so that it can be concluded that better critical thinking ability of student mathematics by using Contextual Teaching and Learning (CTL) learning model compared with direct learning model. Keyword: Contextual Teaching and Learning, The Ability of Critical Thinking